2023
DOI: 10.21278/brod74202
|View full text |Cite
|
Sign up to set email alerts
|

Slow steaming application for short-sea shipping to comply with the CII regulation

Abstract: Slow steaming is an effective operational measure that reduces fuel consumption and thus emissions on board. With the Carbon Intensity Indicator (CII) regulation coming into force in 2023 from the International Maritime Organization (IMO), ships will have to reduce their CO2 emissions even more. The practice of slow steaming is an important measure to comply with this regulation. In this study, real voyage data of a general cargo ship was used. The changes in fuel consumption, CO2, CH4, N2O, and BC emissions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…This finding indicates that herding behavior can lead to reduced efficiency in the transportation system. Moreover, as a high sailing speed generates more emissions [28], the speed-up strategy is a lose-lose strategy regarding the environment and efficiency. To improve efficiency, ship operators are advised to maintain regular sailing speeds and avoid sudden adjustments that can destabilize the system without providing substantial benefits.…”
Section: Herding In the Transportation System Results In Heavier Port...mentioning
confidence: 99%
“…This finding indicates that herding behavior can lead to reduced efficiency in the transportation system. Moreover, as a high sailing speed generates more emissions [28], the speed-up strategy is a lose-lose strategy regarding the environment and efficiency. To improve efficiency, ship operators are advised to maintain regular sailing speeds and avoid sudden adjustments that can destabilize the system without providing substantial benefits.…”
Section: Herding In the Transportation System Results In Heavier Port...mentioning
confidence: 99%
“…The maritime industry, ships and ports, currently relies heavily on fossil fuels as its primary energy source (Zincir, 2022c(Zincir, , 2023. Shifting towards low or zerocarbon fuels is a crucial pathway to achieve decarbonization in shipping (Inal, Charpentier, et al, 2022).…”
Section: Alternative Fuelsmentioning
confidence: 99%
“…Shifting towards low or zerocarbon fuels is a crucial pathway to achieve decarbonization in shipping (Inal, Charpentier, et al, 2022). Currently, liquefied natural gas (Schinas and Butler, 2016), biomass fuels (Sevim and Zincir, 2022Zincir, , 2023, and hydrogen energy (Inal, 2023) are emerging as promising clean alternatives for the maritime sector.…”
Section: Alternative Fuelsmentioning
confidence: 99%
“…The authors concluded that despite the need for additional ships when slow steaming is applied, the operating cost of additional ships is lower than the savings in fuel consumption. Zincir [24] conducted an economic analysis based on real voyage data of a general cargo ship and concluded that when slow steaming is applied, operating costs increase and fuel costs decrease, i.e., the total costs per voyage decrease by approximately 23%. During slow steaming, the ships sail in off-design conditions and their resistance and propulsion characteristics are notably different compared to those at the designed speed [25].…”
Section: Introductionmentioning
confidence: 99%